THE ANALYSIS OF MORAL MESSAGE ON BANTEN’S FOLKLORE AND ITS LEARNING PROCESS OF CHARACTER EDUCATION- ORIENTED AT GRADE SIX SD NEGERI BALARAJA 2 - Suprani Suprani; Nana Hendracipta (JPSD (Jurnal Pendidikan Sekolah Dasar), 2018)
Abstract. The background of problem of this research was occurred due to the student’s lack of identifitying if this folklore (Banten Folklore). The result of learning process of moral massage analysis was only focused on knowledge, and it did not give any significant effect towards student’s behavior and caracters. The formulations of problem for this research were: (1) Is there any moral message on Bnaten’s Folklore (2) Can learning process of Banten’s folklore be described through charahter education- oriented. This research was conducted through qualitative descriptive method.Meanwhile the data collecting technique were conducted test and non- test by using observation. The result of the research showed that the analysis of moral message on Banten’s Folklore entitled “Oath Mosque of Inland Terate” reached 6.20 (fairly good), on “Legend OF Pinang Mountain” reached 7.45 (good), and on “ The Lagend of Kuwung Stone” reached 8.00 (very good) and stories could be concluded contained the moral message. The result of observation showed that character education- oriented the moral message. The toward student’s attitudes and behavior. From the research could be conclude that Banten’s Folklore had its own moral message. The learning process of character education- oriented gave significant effect towards student’s behavior and it also could be applied in their daily life.Keywords: Banten’s folklore, moral message, and character education